Evaluation of Iron and Zinc Contents of Some Fish Species - Karaaslan Ayhan, Nagihan; Yaman, Mehmet (Springernature, 2022)
In this study, Fe and Zn contents in the muscle of different fish species (Engraulis encrasicolus, Trachurus trachurus, Mullus barbatus, Mugil cephalus, Pomatomus saltatrix, Dicentrarchus labrax, Scomber scombrus, Sparus aurata) were determined using flame atomic absorption spectrometry (FAAS). The highest Fe and Zn contents among studied fish species were found in Engraulis encrasicolus (7.13 +/- 0.19 mg/kg) and Sparus aurata (11.00 +/- 0.28 mg/kg). The lowest Fe and Zn contents were determined in Dicentrarchus labrax (3.12 +/- 0.09 mg/kg) and Pomatomus saltatrix (5.50 +/- 0.05 mg/kg). Moreover, the results were evaluated considering the estimated daily intakes (EDI) of these elements for adults. The estimated daily intakes were varied from 0.0101 to 0.0231 mg/kg bw/day for Fe and 0.0178 to 0.0357 mg/kg bw/day for Zn in fish species. In addition, the hazard quotient (HQ) and the hazard index (HI) values were calculated for risk assessment, and it was determined that these values were below 1 for fish species.
Keywords: Element; Food; Dietary intake; Health risk assessment